Analysis of Break Even Point in Tough Factory Businesses in Batu Merah Village, Sirimahu District, Ambon City - Maria Juneferstina (International Forum of Researchers and Lecturers, 2024)
This tofu factory industry has existed since 2000 and in general, the people who set up the tofu factory were originally a meatball seller who had lived in Batu Merah village for a long time. From the beggining, the tofu factory industry was established until now, the industry is still operating and has never done production cost classification, break even point calculations, profit planning calculations, and margin of safety precentage ratios. The purpose of this study was to determine the break-even point that must be achieved in the tofu factory business of Mr. Haji Rahim in Batu Merah Village, Sirimahu District, Ambon City. The results showed that the total cost of production in March 2024 was Rp. 33,400,000 consisting of a total fixed cost of Rp. 27,700,000 and a total variable cost of Rp. 5,700,000. By showing that the total sales of tofu during March 2024 were Rp. 39,200,000. The number of tofu sold during March was 1,120 units with a unit price of Rp. 35,000 per unit.